A Study on the Performance of Mutual Funds of Indian AMCs - Nandini Seal; Soumya Mukherjee (Management Journal for Advanced Research, 2022)
A mutual fund is a pool of money managed by an Asset Management Company (AMC) that collect funds from different individuals as well as institutional investors, and invest those funds in various securities, capital assets such as bonds, real estates, stocks as well as in mutual funds. Most of the Asset Management Companies have different categories of equity mutual funds depending upon the risk associated with such investments. In this case, trailing return and rolling return indicate the performance of a mutual fund. However, a long-term investor has to consider other factors associated with such mutual funds (like asset under management, expenses ratio, number of stocks, and experience of the management) to finalise the selection of mutual funds. In this research paper, an attempt has been made to identify the relationship among the performance of selected equity mutual funds and the parameters considered by the investors for selecting the fund. 't-statistic’ has been used to identify such relationship. This research shows that there is no relationship between trailing return of any kinds of Equity mutual funds and the selected parameters by the investors. However, number of stocks and experience of management have a little impact on the rolling return of equity large cap mutual funds and Assets under management has a little impact on rolling return in case of mid-cap mutual fund only.